Myocardial Enzyme Profile and Short-Term Prognosis of Patients with Prolonged Myocardial Damage after Transcatheter Aortic Valve Replacement - Han, Ke (Journal of Medical Biochemistry, 2025)
AbstractBackground: This work investigated the changes in myocardial enzyme profile (MEP) and short-term prognosis (STP) in patients with myocardial damage (MD) after transcatheter aortic valve replacement (TAVR). Methods: 100 patients receiving TAVR surgery were selected and rolled into an observation group (Obs group, 50 cases) and a control group (Ctrl group, 50 cases) according to postoperative myocardial status. The changes in MEP before and after the TAVR and the STP within 3 days after surgery were compared and analyzed. Results: CK-MB levels were (21.6 ± 8.8) IU/L, (17.2 ± 7.1) IU/L, and (15.2 ± 6.4) IU/L at 12 h, 24 h, and 72 h after TAVR, respectively, in the Obs group; and the cTnT levels were (0.284 ± 0.13) ng/mL, (0.315 ± 0.15) ng/mL, and (0.363 ± 0.22) ng/mL, respectively, at the same time points. The CK-MB and cTnT levels in the Obs group were increased more obviously based on the conditions in the Ctrl group (P
Keywords: aortic stenosis; aortic valve replacement; myocardial enzyme profile; short-term prognosis